A quantum chemistry study of the deoxidation of lignite during hydrothermal dewatering treatment. Issue 3 (14th September 2022) - Zhu, Jiyun; Yu, Yujie; Huang, Rui; Chen, Xingle; Li, Yang
ABSTRACT: To investigate the deoxidation mechanism of lignite under hydrothermal dewatering (HTD) condition, the removal mechanism of carboxyl and methoxy groups was calculated at the B3LYP-D3/6-311 G(d, p) level by using density functional theory. The feasibility of deoxidation was analyzed from the perspective of thermodynamics and kinetics, and the influences of hydrogen bond on the deoxidation process were analyzed. The results showed that the activation energy of decarboxylation was lower than that of demethoxide, indicating that the carboxyl group had high reactivity. Through the hydrogen bonding between the carboxyl group and water, the activation energy of indirect decarboxylation (lignite-C6 H5 -COOH→lignite-C6 H6 -COO→lignite-C6 H6 + CO2 ) decreased by 10 kJ/mol, whereas the activation energy of direct decarboxylation increased by 8 kJ/mol. The activation energy of demethylation was reduced by 25 kJ/mol, and the change in activation energy of subsequent decarbonylation was similar to that of decarboxylation. The two-step elementary reaction benefitted the deoxidation reaction.